Berbagai Faktor yang Berpengaruh Terhadap Struktur Modal dengan Ukuran Perusahaan Sebagai Moderasi (Perusahaan Plastik dan Kemasan) - Mareta Umi Anisak; Meta Ardiana (JFAS : Journal of Finance and Accounting Studies, 2023)
This study proves the effect of business risk, sales growth, asset structure on capital structure which is moderated by company size. This type of research method is quantitative research with purposive sampling. The object of this research is the plastic and packaging sector companies listed on the Indonesia Stock Exchange in 2019-2021. Data analysis uses SPSS version 26 and Moderated Regression Analysis (MRA). The results of this study indicate that the business risk and sales growth variables have no effect on the capital structure. While the asset structure variable affects the capital structure. In addition, company size cannot moderate business risk, sales growth and asset structure to capital structure